2010
DOI: 10.1007/s00432-010-0766-2
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-releasing peptide links stressor to cancer progression

Abstract: GRP is a multi-functional peptide, which acts as a stress mediator as well as a growth factor linking stressor to cancer progression. GRP and its high-affinity receptor are useful targets for the diagnosis and treatment of cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…9,11 Therefore, chronic stress may influence cancer cells by the release of GRP, further activating the sympathetic nerve system and the hypothalamic-pituitary-adrenal axis through the release of stress hormones. 38 Another possibility is that GRP is provided to tumors by PNECs. PNECs are resident lung cells and have been suggested to be the cell of origin for some SCLCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11 Therefore, chronic stress may influence cancer cells by the release of GRP, further activating the sympathetic nerve system and the hypothalamic-pituitary-adrenal axis through the release of stress hormones. 38 Another possibility is that GRP is provided to tumors by PNECs. PNECs are resident lung cells and have been suggested to be the cell of origin for some SCLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors often resemble integrated organs, being composed by different cells, which work coordinately. Although both central and sympathetic nerve elements are present in different types of tumors, 38 little is known regarding the roles they play. Sympathetic nerve fibers that reach tumors can release neurotransmitters and neuropeptides locally, 12 activating signaling pathways that can facilitate tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of GRP-R with GRP influences a wide range of physiological processes including thermoregulation, gastric and pancreatic secretion, stress responses, and food intake and satiety [3]. Increasing evidence has suggested that GRP and its receptor act as a mitogen, morphogen, and proangiogenic factor in many types of cancer, and an inflammatory mediator in inflammatory cells and vascular cells [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The BBN-based peptides, having high binding affinity to GRP receptor, could serve as the specific ligand for tumor diagnosis. Hence, the design and development of the new diagnostic or therapeutic conjugates based on BBN has made headway in recent years (22,23). Prasanphanich et al designed radiolabeled BBN conjugates as effective diagnostic/therapeutic targeting vectors for PC-3 human cancers (24).…”
Section: Introductionmentioning
confidence: 99%